The complex relation between obstructive sleep apnoea syndrome, hypogonadism and testosterone replacement therapy - Graziani, Andrea; Grande, Giuseppe; Ferlin, Alberto (Frontiers in Reproductive Health, 2023)
Obstructive sleep apnoea syndrome (OSAS) is an under-recognized medical disease. The main risk factors for OSAS are male sex, older age, obesity, and metabolic syndrome, that are also associated with male hypogonadism (MH). Therefore, obesity has been classically identified as the most evident link between OSAS and MH. However, OSAS is per se linked to the development of MH by a combined effect of hypoxia, increased night-time awakenings, reduced sleep efficiency and fragmented sleep. Similarly, MH might represent a risk factor for OSAS, mainly related to sleep disturbances that are frequently associated with low testosterone. Data on testosterone replacement therapy (TRT) in patients with OSAS are limited. Nevertheless, TRT is generally contraindicated by guidelines in the presence of untreated or severe OSAS. TRT might in fact worse OSAS symptoms in different ways. Furthermore, OSAS has been proposed to be a risk factor for secondary polycythaemia and TRT might exacerbate polycythaemia. Therefore, TRT in hypogonadal men affected by untreated OSAS or severe OSAS should be considered with caution and in a personalised way. Nevertheless, the type and dosage of TRT should be considered, as short-term high-dose TRT might worsen OSAS, whereas long-term lower doses could eventually determine a clinical improvement of symptoms of OSAS. Here we reviewed the data on the association between OSAS, MH and TRT, including the opportunity of assessment of patients who develop signs and symptoms of OSAS during TRT by polysomnography.